End-member analysis of the grain size of surface sediments used to synthesize Holocene aeolian activity across the Ordos Plateau in northern China - Bing Liu; Heling Jin; Hui Zhao; Jianhui Jin; Aijun Sun; Xingfan Wang; Xiaomei Zhang; Jianhui Ge; Yujie Xu; Jianbao Liu (Geoderma, 2025)
The deserts of northern China comprise a major terrestrial ecosystem in the middle latitudes of the Northern Hemisphere, and aeolian activity and dust emissions of these deserts have affected the evolution of climate and ecosystems on both continental and global scales. However, previous reconstructions of Holocene aeolian activity within this region are controversial due to the erosional susceptibility of the dunefields on the Asian summer monsoonal boundary (ASMB), the diverse proxies used to reconstruct aeolian dynamics, and the spatial heterogeneity of the sedimentary environment across the various studied archives. Using the spatiotemporal substitution approach, we developed a new proxy of aeolian activity based on end-member analysis (EMA) of the grain size of surface samples from various types of aeolian deposit. We then applied the results to six aeolian sand-palaeosol sequences on the Ordos Plateau to reconstruct Holocene aeolian activity. We then produced a synthesis of regional aeolian activity based on records from sedimentary sequences, with their ages constrained by luminescence dating, and quantitatively estimated the contributions of various environmental factors. The results indicated that components EM2 + 3 are transported mainly via saltation and creep, and their abundances gradually increase with increases in the intensity of aeolian activity and decreasing vegetation cover. Our regional synthesis demonstrated that the strongest aeolian activity was in the Early Holocene, especially during 12–10 ka, whereas it was weakest during 7.5–3.5 ka and especially during 6–5 ka; however, strong aeolian activity was renewed at ∼ 2–1 ka. These findings agree with the integrated results from typical dunefields in the eastern-central parts of the ASMB. Quantitative analyses of the potential drivers indicated that vegetation cover was the principal control on Holocene aeolian activity. This finding emphasizes that protecting the natural vegetation cover should be the principal measures used to combat aeolian activity in this region.